Analysis of Agreement Between Computed Tomography Measurements of Glenoid Bone Defects in Anterior Shoulder Instability With and Without Comparison With the Contralateral Shoulder. (December 2015) - Milano, Giuseppe; Saccomanno, Maristella F.; Magarelli, Nicola; Bonomo, Lorenzo
Background: Computed tomography (CT) is frequently used to diagnose glenoid bone defects in anterior shoulder instability. The assessment of glenoid defects on 2-dimensional (2D) and 3-dimensional (3D) CT scans has been reported with and without a comparative study of the contralateral shoulder; however, no previous studies have analyzed if these 4 methods agree. Purpose: To estimate agreement between CT assessments of glenoid defects by examination of the affected shoulder alone and by comparison with the contralateral side on both 2D and 3D CT scans. Study Design: Cohort study (diagnosis); Level of evidence, 2. Methods: A total of 200 prospectively enlisted patients affected by unilateral anterior shoulder instability underwent CT of both shoulders. The area of the missing glenoid was calculated on 4 sets of CT scans (2D and 3D CT images with and without comparison with the contralateral shoulder) by using the circle method. Agreement between the 4 measurements in quantifying the bone defect was estimated according to the Bland-Altman method. Agreement between the 4 measurements in assessing the presence and type of defect (fracture or erosion) was analyzed with κ statistics. Results: Analysis of agreement between CT measurements in quantifying glenoid bone defects showed that the mean difference between the 4 measures was less than 1% of the area of the inferior glenoid in each pairwise comparison. Limits of agreement were always below the established acceptable limit of 5%. The assessment of the presence and type of bone defect showed strong to near-complete agreement between the 4 measurement methods. Conclusion: CT assessments of glenoid bone defects with and without comparison with the contralateral shoulder showed very good agreement in identifying the size, presence, and type of defect in patients with anterior shoulder instability on both 2D and 3D CT scans.